Callas phenomenon - Drach, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. The 100th anniversary of the birth of Maria Callas became an occasion to look at the world of opera through the prism of her talent and artistic destiny, to pay attention to the presence of her image in modern culture, to reconsider life lessons in art left by the "diva century". The main objective of the study is to reveal the semantic structure of the almost limitless discourse about the great opera singer through certain aspects of the coverage of the "Kallas phenomenon" in modern culture. The methodology includes ideas and musical-analytical approaches to the coverage of the stage practice of M. Cherkashina-Gubarenko, considerations of phenomenologists, in particular certain provisions of R. Barthes's "practical mythology", M. Foucault's "archeology of knowledge", M. Dolar's "phonocentrism" (2022), which are included in the framework of the holistic-integrative method developed by A. Samoylenko. Results and conclusions. Maria Callas (1923 - 1977) is considered as a key figure in the renewal of the operatic tradition. On the basis of published materials, research and audio sources, an attempt is made to understand the vectors of thematization of her life and creativity in the space of modern culture. Confidence in the public consciousness of the cultural phenomenon La Divina, which marked the emergence of the singer in the "big time" of history as an actor of symbolic significance, can be traced from the fixation and acceptance of the characteristic features of her voice (interpreted in Western culture as a metaphor for the "self" of the human personality) through the identification of a dominant intentions in the interpretations of opera parts (which explains the specificity of individual and personal accents in the performance of this or that role) to the establishment of markers of her public image in the mass communication system and, ultimately, the definition of the semantic load that the modern myth of Callas assumes. These interconnected aspects of the coverage of the "Callas phenomenon" made it possible to reveal the semantic structure of the almost limitless discourse about the great opera singer, diagnosing the presence of a certain thematic core in it, which is actually identified with the archetypal "signs" of the opera - the images of la innamorata and la abbandonata. The tension that arises between these existentials personifies the artistic individuality of M. Callas. Her virtuoso balancing between these "modes of being" on stage, in private and public life, on the one hand, as an object of various reflections/receptions, ensures the integrity and self-identity of the "Kallas phenomenon" in all its manifestations, on the other hand, he asks the general frame in which the essence of the opera as such is revealed.